An Evaluation study for ICT (Information & Communication Technology) book for the 2end high school grade with its both branches (scientific and literary) by the teachers (Field Study in Lattakia City) - أحمد مطيعة; معوض فائز (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aims to identify the evaluation of teachers for Information Technology book for the second high school grade with its both branches (scientific and literary), it also aims to identify the differences between teachers according to a group of variables. In order to answer the questions of this research and to find the indications of differences in teachers’ evaluation about the dimensions and core of Information Technology book according to (specialty, gender and year of experience). The researcher has prepared a questionnaire that consists of 47 units distributed on 7 cores. This questionnaire has been applied on 16 male and female teachers of Information Technology book for second high school grade (scientific and literary) in the city of Lattakia. The results of this research as shown that the teachers’ estimations of the book are high and that there are no statistical differences at the rate of 0.05 between teachers according to (specialty, gender and years of experience). This research had advised to do more researches to explore the abilities and skills of teachers in dealing with technological educational curricula. It has also focused on the importance of conducting condensed training courses to know the quality of the developed curricula and methods of their application.